2016
DOI: 10.1371/journal.pone.0152530
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity of β-Diketone Antibiotic Mixtures to Zebrafish (Danio rerio) by Transcriptome Analysis

Abstract: Fluoroquinolones and tetracyclines are known as β-diketone antibiotics (DKAs) because of bearing a diketone group in their molecular structure. DKAs are the most widely used antibiotics to prevent generation of disease in humans and animals and to suppress bacterial growth in aquaculture. In recent years, overuse of DKAs has caused serious environmental risk due to their pseudo-persistence in the environment, even though their half-lives are not long. So far, no reports were concerned with the joint immunotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…To date, little information is available for the above-mentioned lncRNAs and therefore the results of this study can enrich the functional database of lncR-NAs. Based on previous immune toxicity research on DKAs by our group (Li et al, 2016a), the transcriptional changes demonstrated for plk3 and syt10 in this study appear to be associated with immune functions and are regulated by the above 3 lncRNAs. The histopathological observations further support our understanding of DKA response to immune toxicity mechanisms.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…To date, little information is available for the above-mentioned lncRNAs and therefore the results of this study can enrich the functional database of lncR-NAs. Based on previous immune toxicity research on DKAs by our group (Li et al, 2016a), the transcriptional changes demonstrated for plk3 and syt10 in this study appear to be associated with immune functions and are regulated by the above 3 lncRNAs. The histopathological observations further support our understanding of DKA response to immune toxicity mechanisms.…”
Section: Discussionsupporting
confidence: 66%
“…Zebrafish in control (0 mg/L) and treatment (6.25 and 12.5 mg/L) groups were randomly selected after DKA exposure at 90 dpf and rinsed with phosphorous buffer solution. The anatomy of the whole fish and total RNA extraction were characterized as detailed in our previous report (Li et al, 2016a). After the quantity and purity of total RNA were determined, the rRNA was removed using a epicentre Ribo-Zero TM kit (Illumina Company, Madison, WI, USA) to recover and purify the remainder of the rRNA depleted RNA (polyA+ and polyA−).…”
Section: Total Rna Extraction and Lncrnas Library Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…2014; Li et al . 2016) and excessive dietary dose (Toften & Jobling 1996). In these studies, treated fish had delayed and premature hatching (Zhang et al .…”
Section: Body Malformation and Damagementioning
confidence: 99%
“…In real-world environments, residual components of antibiotics are very complex and may contribute to joint (i.e., interactive) toxicological effects (Ding et al, 2013;Melvin et al, 2014). Our previous research examined the effects of three representative FQs (enrofloxacin, ofloxacin and ciprofloxacin) and three TCs (chlortetracycline, oxytetracycline and doxycycline) on joint toxicity to various tissues and organs including the immune, reproductive and nervous systems in zebrafish (Danio rerio) (Li et al, 2016a). Some FQ family members, such as ciprofloxacin (Etminan et al, 2017;Samarei et al, 2014), are reported to cause ototoxic effects, while some TC family members, such as doxycycline (Chotmongkol et al, 2012) and minocycline (Corbacella et al, 2004) function to restore hearing loss.…”
Section: Introductionmentioning
confidence: 99%